NANO-GOLD PARTICLES MEDIATED DETECTION OF NS1; AN EARLY DIAGNOSTIC MARKER OF DENGUE VIRUS INFECTION - A. Hussain; S. U. Rehman; S. Aslam; N. Javed; Z. Abbas (Journal of Animal and Plant Sciences, 2014)
In this study, an immunoassay is developed for qualitative determination of NS1 antigen of dengue virus in serum using nano-gold particles. This diagnostic device comprises of four components such as sample pad, conjugation pad, nitrocellulose membrane and absorbent pad. Anti-NS1 antibodies and rabbit anti-mouse IgG antibodies were coated on nitrocellulose membrane as a test and control line respectively. Assay device was evaluated by purified NS1 and prior ELISA confirmed NS1 positive and negative samples. The diagnostic device showed promising results to detect NS1.
Keywords: Dengue Virus; Diagnostic Device; Colloidal Gold Particles; Rapid Diagnosis; NS1 antigen; ELISA